AN ANALYSIS OF SYNTACTICAL ABILITY OF SECOND LANGUAGE CHILDREN AGE 5-6 YEARS OLD IN TAMAN KANAK-KANAK (TK) PARA BINTANG KOTA JAMBI - afif rofii (Universitas Batanghari Jambi, 2017)
The purpose of this research is to identify syntactical ability of second language children age 5-6 years old. The subject of the research is learners of Kindergarten Para Bingtang Kota Jambi. This research is qualitative by using descriptive method. The result of the analysis shows that children age 5-6 years old in Para Bintang Kota Jambi have an ability to produce single sentence and complex sentence. Furthermore, they are also capable of using affirmative sentence, interrogative sentence, imperative sentence, and exclamation sentence. The ability of second language of children is still influenced by mother tongue which shows code mixing and code switching in their utterances. The children will choose to use second language which is Indonesian language in their interaction with teacher. Meanwhile, the children will use mother tongue which is Malay language in communicating with fiends of the same age. The children age 5-6 have an ability to produce sentences from second language and use it based on the context of their communication. Keywords: Language Acquisition, Syntactical Ability, Mother Tongue, Second Language.